Karakterisasi oktaasetat c-metil kaliks[4]resorsinarena sebagai ionofor membran elektroda selektif ion kalium = Characterization of Octaacetate of C-Methyl Calix[4]Resorcinarene as Membrane Ionophore of Potassium Ion Sel - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
A study on the characterization of potassium ion selective electrode had been done. Octaacetate of C-methyl calix[4]resorcinarene was used as ionophore component of a polymeric liquid membrane ion selective electrode (ISE), with polyvinyl chloride (PVC) as a membrane matrix, dioctyl sebacate (DOS) as a plasticizer or membrane solvent, and potassium tetrakis(pchlorophenyl) borate as an anionic additive. The quality of the ISEs was characterized by potentiometric selectivity coefficient, Nernst factor, dynamic range of measurement, and response time of the ISE membrane. The potentiometric selectivity coefficient was evaluated by separated solution method (SSM) with both main and interfering ions concentration of 0.1 M. The Nernst factor and dynamic range of measurement was determined by measuring the potential cell (emf) in - 10-5 M concentration of main ion (potassium ion). The response time was evaluated by measuring the potential cell (emf) toward times in the dynamic range concentration. The result of research showed that the membrane responded selectively to potassium ion in the presence of interfering ions : ammonium, sodium, zinc, magnesium, barium, lead, and nickel ion. The value of Nernst factor of the membrane was 36.8 mV per decade, with the dynamic range of 10-5-10-2 M and average of response time of 2.9 minute.